TINJAUAN HUKUM ISLAM TERHADAP SANKSI PIDANA PENCABULAN YANG DILAKUKAN OLEH ANAK DIBAWAH UMUR MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2014 - Karuniawan , Fathony; Adnan, Idul; Nuriskandar, Lalu Hendri (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2022)
Children who violate the law or commit criminal acts are greatly influenced by several other factors outside the child, such as relationships, education, playmates and so on. Because criminal acts committed by children are generally a process of imitating anything influenced by negative actions from adults or those around them. What factors influence the occurrence of criminal acts of sexual immorality committed by minors, internal factors, namely intelligence factors, age factors, gender factors, while external factors, namely household factors, educational and school factors, children's social factors and social media factors in resolving criminal acts of obscenity. committed by minors and criminal sanctions for perpetrators of sexual abuse against children according to Law Number 35 of 2014 can be implemented by the Panel of Judges by applying Article 82 of Law Number 35 of 2014 and Article 290 paragraph 2 of the Criminal Code, if the defendant is proven to fulfill the objective and critical elements. subjective nature contained in these two articles carries a maximum penalty of 15 years in prison and a minimum of 3 years in prison. According to the view of Islamic law, the implementation of criminal sanctions against perpetrators of sexual abuse against children can be applied ta'zir,